Réflexions d’Inuit en contexte post-colonial : des identités culturelles en marche - Natacha Roudeix (Lengas)
This article explores the existing dynamics between languages and identities in a changing multilingual indigenous context in Nunavik. Although immersed in Inuit culture throughout their lives, many Inuit today do not understand or speak their ancestral language, Inuktitut. This ethno-sociolinguistic study (Blanchet, 2012) exposes Inuit cultural and linguistic experiences which revealed that by actively participating in their Inuit way of life, young and old alike learn to live their “inukness” (Qilavaaq, 2012), the Inuit way to say, act, think and live. An identity cultivated through the myriad practices that make up the Inuit oral tradition. I examine the emerging representations of Inuit participants through the way they expressed their experiences in their ancestral culture. Culture which, today, is undergoing significant sociolinguistic changes (Weinreich, 1953; Thomason & Kaufman, 1988; Wendel & Heinrich, 2012; McCarty & Nicholas, 2014).